2020
DOI: 10.1111/ajt.16073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 10 years of parainfluenza virus, human metapneumovirus, and respiratory syncytial virus infections in lung transplant recipients

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 44 publications
(105 reference statements)
3
25
3
Order By: Relevance
“…HMPV is a single-stranded RNA virus of the Pneumoviridae family, closely resembling RSV. Its seasonality also follows that of RSV, with most cases identified in the winter and spring [71]. Studies conducted on LTRs identified HMPV in 3.6-6.8% of positive respiratory samples [1,2,6,72].…”
Section: Human Metapneumovirusmentioning
confidence: 95%
See 4 more Smart Citations
“…HMPV is a single-stranded RNA virus of the Pneumoviridae family, closely resembling RSV. Its seasonality also follows that of RSV, with most cases identified in the winter and spring [71]. Studies conducted on LTRs identified HMPV in 3.6-6.8% of positive respiratory samples [1,2,6,72].…”
Section: Human Metapneumovirusmentioning
confidence: 95%
“…It seems, however, that there is no definitive association between rhinoviruses and CoVs and rejection or CLAD [72,125]. Treatment with ribavirin was associated with lower rates of CLAD/BOS in LTRs with RSV, HMPV and PIV infections, as shown in a study on 139 LTRs where ribavirin was associated with a lower risk of CLAD (OR 0.24, 95% CI 0.1-0.59) [71].…”
Section: Respiratory Viruses and Rejection In Lung Transplantationmentioning
confidence: 99%
See 3 more Smart Citations